Uma análise exploratória da indústria de serviços PWLAN Wi-Fi no Brasil: em busca de uma vantagem competitiva sustentável - Dusi Filho, Antonio Alvim (2004)
The telecommunications industry worldwide is advancing very fast in new technologies and standards’ offerings enabling and providing flexibility to information transmission/reception between people and the Internet. Specially, in regards to mobility, wireless devices like mobile phones and PDAs (Personal Digital Assistant) have been facilitating companies to reach out their customers anytime, anywhere. Many wireless communication standards have been emerging, initially in the mobile industry, and lately in the computer/PDA industry, enabling wireless broadband data communications and mobile commerce (m-commerce). Specially, the Wi-Fi standard has been spreading out worldwide thru the expansion of public wireless local area networks (PWLANs). Therefore, telecommunication vendors, mobile operators and ISPs have been demonstrating a big interest in this area due to the new opportunities for revenue increase. All these aspects of Wi-Fi’s recent history have been generating several questions regarding the technology’s future success and it’s ability to create sustainable competitive advantages, in spite of the continuous growth in business related to this technology. The objective of this study is to analyze the Brazilian Wi-Fi PWLAN market, identifying key players and business models used by them, comparing them to the business models identified by Shubar and Lechner. This study also intends to evaluate these companies and respective business models according to the VRIO framework methodology developed by Barney, which is based on the Resource Based View theory (RBV).